GAMBARAN PENGETAHUAN IBU TENTANG MANFAAT TIMBANG BAYI SECARA RUTIN DI DESA JAMBAKAN KECAMATAN BAYAT KABUPATEN KLATEN - Kiki Astuti; Kemaludin .; Sri Redjeki (STIKES DUTAGAMA KLATEN, 2015)
Background: Development of comunity nutritional status can be monitored based on the recording and reporting (RR) of public nutrion improvement program which is reflected in the result of a babies weigh every month in ihc . in 2013 the total of children under five that weighed as much as 67,766 (77,8%) of the 87,072 children under five. Tended to decline compared in 2012 which covors 81,1%. Purpose: To decribe the mothers knowledge about the benefit of babies weigh routinely in jambakan village, bayat district , klaten regency. Method: This reseach is qualitive descriptive reseach with cross sectional approach . the population in the reseach are all mother have bables 0-12 month in jambakan village, bayat district, klaten regency by 39 informants. Technique of sampling used quota sampling with is informant instrument in the research are guidelines for focus gruop , interview, questionnaire. Result: The mothers knowledge about of benefit of babies weigh routinely in jambakan village, bayat district,klaten regency in interview with good category (0%), enough category (40%), bad category (60%). mothers knowledge about the benefit of babies weigh in bad category (50%), concern mothers to bebies weigh rotnely in good category (100%). Conclusion: The description of mothers knowledge about the benefit of bebies weigh routinely with bad category (50%).